Development of A Web-Based Physical Education Learning Media Model at Senior High School Muhammadiyah 3 Palembang - Nurmulkiah, Ismah; Iyakrus, Iyakrus; Syamsuramel, Syamsuramel (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
This research aims to produce a web-based application model as an application that students can use in physical education learning at school. The method used in this research is the R&D (research and development) method, namely a research method that aims to produce products and test the validity and effectiveness of these products in their application. This research is a development of Borg & Gall. Judging from the validation results by several validators, the average score from all aspects of the assessment is 3.48 in the valid category. The detailed score for each aspect consists of 3.7 for the material aspect, 3.27 for the media aspect. The level of practicality and level of effectiveness of web-based physical education learning media is in accordance with the independent curriculum. This means that the web-based physical education learning media for class XI is in accordance with the independent curriculum and the syllabus is declared valid after looking at it from all aspects.